(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Geographical indications (GIs) allude to items with explicit attributes, features or notorieties coming about because of their geological beginning. This separates items in light of remarkable neighborhood elements, history or particular qualities connected to normal and human variables, like soil, environment, nearby ability, and customs. GIs are perceived as intellectual property rights (IPRs) as well as thusly provide both a supportive promoting device and insurance of the name. GIs can be utilized to encourage sustainable food systems and sustainable development (SD)by subsequent Food and Agriculture Organization of the United Nations (FAO) practice of the virtuous ring of origin-linked quality. On the off chance that they live up to their capability to advance financial turn of events and food security, they could give a promising regional way to deal with accomplishment of the Sustainable Development Goals (SDGs). In this perspective, assuring economic feasibility is crucial, although there is scant empirical validation of the advantages of GIs, particularly in nations where GI processes are relatively new. Commencement with the authorizedacknowledgement of a GI as well as the stages that follow, this research aims to offer empirical validation on the economic effects produced by the GI procedure. It examines nine cases with a focus on the food industry and provides a range of local value chains and national contexts. The strategy takes into account "operational" GI procedures: such where a training code (or determinations) is characterized and the GI is utilized as well as overseen by an aggregate association.